Microbial diversity in honey from different ecological zones and its impact on honey quality and bee health - ANDI GITA MAULIDYAH INDRASWARI SUHRI; FITHA FEBRILIA RULI; WA ODE KAMILLAH; SYAHRIBULAN SYAHRIBULAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Suhri AGMI, Ruli FF, Kamillah WO, Syahribulan. 2025. Microbial diversity in honey from different ecological zones and its impact on honey quality and bee health. Biodiversitas 26: 3316-3323. Microbial communities in honey play a critical role in determining both honey quality and bee health. However, how these communities shift across ecological gradients remains poorly understood. The aim of this study was to provide the first comprehensive comparison of honey-associated microbial diversity across forest, agricultural, and urban zones in South Sulawesi, Indonesia. Results from high-throughput sequencing, physicochemical analysis, and pathogen inhibition assays revealed that honey from forest areas had significantly higher microbial diversity, dominated by beneficial taxa such as Lactobacillus and Bifidobacterium. These microbes were positively associated with enhanced honey quality, reflected in higher phenolic content, antioxidant capacity, and lower moisture levels, and exhibited strong antagonistic activity against key bee pathogens (Nosema ceranae, Paenibacillus larvae). In contrast, urban honey showed reduced microbial richness, increased prevalence of stress-tolerant genera like Pseudomonas, and diminished bioactivity. Seasonal sampling confirmed that these trends were consistent across different climatic periods. Furthermore, probiotic isolates from forest honey demonstrated superior pathogen suppression, suggesting functional microbial benefits associated with ecologically intact habitats. The study also found statistically significant correlations between microbial diversity and physicochemical parameters using PERMANOVA and PCA. These findings demonstrate that habitat degradation can alter honey microbial profiles, with cascading effects on product quality and pollinator resilience. By linking ecological context with microbial function, this study underscores the ecological importance of preserving biodiverse landscapes for sustainable apiculture and bee health management.